Internação involuntária e o abuso de substâncias psicoativas - o pathos familiar - Ferreira, Frederico Guerreiro (2016)
The use and abuse of Psychoactive Substances (PAS) in contemporaneity corresponds to a social issue and a public health issue. Few social phenomena entail more costs with justice and health, family difficulties, and appearances in the media than the PAS abuse comsumption. The government power has been facing this situation allocating investments and developing public policies. Despite the current Mental Health Policy, based on the principles of Psychiatric Reform that prioritizes outpatient services, the number of investments from various government spheres and families requests for admissions continue increasing. This study aimed to understand the pathos experienced by an individual toward the involuntary internment of a family member who is an abusive user of PAS. The research also aimed to investigate what led that individual to choose this type of treatment. The Psychoanalysis was the theoretical basis of this work, and the exercise of the psychoanalytic method, from the collection of bibliographic references up to the interpretation of the semi-structured interview, conducted in depth, was intended. The findings of this research gave us the oportunity of thinking about how the social callings to the family were made, especially in regard of atention and care with their family members who are user of PAS and how it affects this family individual. It also allowed to discuss how the public policies that preconize involuntary internment, affectivity, prohibitionist and mono-disciplinarity – that cross the State in the attention given to this issue – are formulated and implemented. The interview analysis showed us how happen the agencying of pathos, the libidinal aspects of joy and guilt, the desire to punish and atonement, working in family relations and in caring relations, especially in the decision for involuntary internment. The survey also made possible to understand how a mother, facing the chaotic scene of public health, helpless, finds in the involuntary internment a way to reverberate her affections.